Outsourcing and offshoring in the 21st century : a socio-economic perspective - Kehal, Harbhajan S., 1942-; Singh, Varinder P., 1974- (Idea Group Pub., 2006)
"This book discusses the economic impacts of outsourcing and off shoring to the developing countries and developed countries and the short term and long term implications"--Provided by publisher
Keywords: Contracting out.; Offshore outsourcing.; elektronické knihy; electronic books